Aplicação web integrada ao software R para análise espacial e geração de mapas temáticos em agricultura de precisão - Dall'Agnol, Rodrigo Werner (2017)
The development of agricultural technologies that make it possible to increase productivity and reduce the cost of production, achieving greater profitability is the goal of producers and researchers from all over the world. Using precision agriculture as a base for application of technologies in the field, this study presents the development and implementation of a computational tool in the web environment for spatial analysis of agricultural data and generation of thematic maps.The software allows the automatic selection of parameters of the semivariogram in the geostatistical analysis step and the indication of the best adjusted model, and it is not necessary to manually adjust the models to the experimental semivariogram. From the integration with the statistical software R, using the data of physical and chemical attributes of the soil and the productivity of three farms, the geostatistical analysis and conventional statistics and the generation of thematic maps were performed using interpolation techniques known as kriging and the inverse of the elevated distance to a power. The comparison with commercial software showed that the tool developed in the research is an interesting option for generating thematic maps to provide information on the spatial and temporal variability of soil and plant attributes, thus enabling a more assertive decision making by the producers to correct the analyzed attributes.